Single cell polarity in liquid phase facilitates tumour metastasis - Lorentzen, Anna; Spaich, Saskia; Utikal, Jochen; Sprick, Martin; Trumpp, Andreas (Nature Communications, 2018)
Polarisation of metastasising cancer cells in circulation has not been investigated before. Here the authors identify single cell polarity as a distinct polarisation state of single cells in liquid phase, and show that perturbing single cell polarity affects attachment, adhesion, transmigration and metastasis in vitro and in vivo.